1996
DOI: 10.1021/tx9500843
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PCB Adducts by the 32P-Postlabeling Technique

Abstract: The purpose of this study was to determine whether lower chlorinated biphenyls would be bioactivated to electrophilic metabolites by microsomes alone or in combination with peroxidase. Monochloro- and dichlorobiphenyls were incubated with liver microsomes of rats treated with phenobarbital and beta-naphthoflavone, an NADPH-regenerating system, and deoxyguanosine 3'-monophosphate (dGp). The resultant adducts were analyzed by 32P-postlabeling either following microsomal incubation alone ("preoxidized") or couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 45 publications
1
55
1
Order By: Relevance
“…The metabolism of PCB3 by cytochrome P-450 seems to involve arene oxide intermediates (McLean et al, 1996b). These are converted to mono-hydroxy metabolites and in further steps, probably through a secondary arene oxide intermediates, from the mono-to the di-hydroxy forms (Figure 3).…”
Section: Influence Of Cyps On Metabolic Activation Of Lower Chlorinatmentioning
confidence: 99%
“…The metabolism of PCB3 by cytochrome P-450 seems to involve arene oxide intermediates (McLean et al, 1996b). These are converted to mono-hydroxy metabolites and in further steps, probably through a secondary arene oxide intermediates, from the mono-to the di-hydroxy forms (Figure 3).…”
Section: Influence Of Cyps On Metabolic Activation Of Lower Chlorinatmentioning
confidence: 99%
“…Overwhelming evidence shows that the PCBs are not mutagenic (9). DNA binding has been reported in some crude studies (10), although a specific nucleotide adduct has not been identified (11)(12)(13)(14)(15).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Formation of protein and DNA adducts was observed in vitro with PCB-3 and the tetrachlorinated congeners PCB-47, PCB-49, PCB-52, and PCB-77 (Wyndham et al, 1976;Shimada & Sawabe, 1984). DNA-adduct formation was also observed with a series of 15 mono-and dichlorinated PCBs, with but not without activation by microsomes, horseradish peroxidase and hydrogen peroxide (McLean et al, 1996b). This suggested that quinones were the ultimate genotoxic agents.…”
Section: (B) Binding To Dna and Proteinmentioning
confidence: 99%
“…Rodent and human liver microsomes produced similar or different adduct patterns depending on the PCB congener used, indicating that species differences exist. Reactive intermediates can bind to cellular macromolecules, including DNA and DNA-maintenance proteins, and such adducts can be detected in multiple organs (Morales & Matthews, 1979;Amaro et al, 1996;McLean et al, 1996b;Oakley et al, 1996aOakley et al, , 1996bLin et al, 2000;Pereg et al, 2001Pereg et al, , 2002Srinivasan et al, 2002;Arif et al, 2003;Zhao et al, 2004;Bender et al, 2006;Bender & Osheroff, 2007).…”
Section: (Ii) Cell Culture Tests and In-vivo Assaysmentioning
confidence: 99%